Testing for Persistence in Real House Prices in 47 Countries from the OECD Database - Guglielmo Maria Caporale; Alfonso Dominguez; Luis Alberiko Gil-Alana (CESifo GmbH, 2025)
This paper provides a comprehensive analysis of persistence in real house prices at the quarterly frequency in 47 countries from the OECD Database using fractional integration methods. The sample period varies depending on data availability, the longest series being the Japanese one (from 1960Q1), with the last observation at the end of 2023 or in early 2024 in all cases. Both linear and non-linear models are considered. In the latter case structural break tests are carried out first to capture sudden parameter shifts, and then a specification based on Chebyshev polynomials in time is also estimated in order to allow for smoother changes. The results generally indicate a high degree of persistence, some slight evidence of mean reversion being found only when allowing for non-linearities.
Keywords: C22; E21; 330; real house prices; fractional integration; persistence; trends; non-linearities; structural breaks